A mechanism‐based pain sensitivity index to characterize knee osteoarthritis patients with different disease stages and pain levels. (29th December 2014) - Arendt‐Nielsen, L.; Egsgaard, L.L.; Petersen, K.K.; Eskehave, T.N.; Graven‐ Nielsen, T.; Hoeck, H.C.; Simonsen, O.
Abstract Background In a cohort of well‐characterized patients with different degrees of knee osteoarthritis (OA) and pain, the aims were to utilize mechanism‐based quantitative sensory testing (QST) to (1) characterize subgroups of patients; (2) analyse the associations between clinical characteristics and QST; and (3) develop and apply a QST‐based knee OA composite pain sensitivity index for patient classification. Methods Two hundred seventeen OA pain patients and 64 controls were included. Kellgren and Lawrence (KL) grading scores were obtained, and pressure pain thresholds (PPTs), temporal summation of pain to repeated painful pressure stimulation and conditioning pain modulation (CPM) were assessed. Associations between pain score/area/duration, radiological findings and QST‐related parameters were analysed. A pain sensitivity index was developed and applied based on PPT, temporal summation and CPM. z‐Score, as statistical tool, was calculated for statistically comparing the pain index of a single patient with a healthy control group. Results High knee pain associated with low KL grade showed particular signs of pain sensitization. Patients showed significant associations between clinical knee pain intensity/duration and lowering of knee PPTs (p < 0.01), facilitation of temporal summation (p < 0.01), reduction of CPM function (p < 0.01) and high pain sensitivity index (p < 0.01). The index classified 27–38% of the OA patients and 3% of the controls as highly sensitive with no association to KL. The index increased for high knee pain intensities and long pain duration. Conclusions Radiological scores, contrary to clinical pain intensity/duration, were poorly associated with QST parameters. The pain sensitivity index could classify OA patients with different degrees of OA and pain.